(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. Boron-phosphate glasses with unique properties are widely investigated for medical applications. Regulation of molar ratios of glass-formation components and doping with other ions can be useful approaches for influence on functional properties including of dissolution process at using in the biosystems. The purpose of the work is synthesys of boron-phosphate glasses in sodium-containing systems, their characterization and investigation of dissolution character in model solution for evaluation of their application perspective in clinical practice. Methods. The high-temperature melting of stoichiometric mixture with necessary composition with further fast cooling method was used for synthesis of glasses. Methods of powder X-ray diffraction and IR spectroscopy were used for characterization of glasses as well as thir influence on pH of model solution (pH = 7,45, temperature 37 °C) depending on ther composition was also evaluated. Results. X-ray diffraction results confirmed their amorphous nature, while FTIR spectroscopy established the influence of the borate component and sodium on the depolymerization of the phosphate chain with stabilization of diphosphate fragments in a sodium-enriched section with a molar ratio of Na2O/(P2O5+B2O3) = 60 : 40. It has been shown that the use of glasses with a variable chemical composition: the content of the main component and the P2O5/B2O3 ratio can provide local regulation of the pH of the environment from 5,5 to 9,8, which is important when using them as components of drug carriers, the release of which is regulated by a change in pH. Сonclusions. Optimized conditions for obtaining sodium-containing boron-phosphate glasses, as well as the results of their in vitro testing in a model solution, can be used in the development of materials for medical purposes.